Clinical and laboratory differences between chromosomal and undefined causes of non-obstructive azoospermia: A retrospective study - Luísa Riccetto; Tarsis Paiva Vieira; Nilma Lucia Viguetti-Campos; Tais Nitsch Mazzola; Mara Sanches Guaragna; Helena Fabbri-Scallet; Maricilda Palandi de Mello; Antonia Paula Marques-de-Faria; Andrea Trevas Maciel-Guerra; Gil Guerra Junior (São Paulo Medical Journal, 2022)
ABSTRACT BACKGROUND: Knowledge of clinical and laboratory differences between chromosomal and undefined causes aids etiological research on non-obstructive azoospermia. OBJECTIVE: Compare clinical and laboratory differences between men with non-obstructive azoospermia due to chromosomal anomalies versus undefined causes DESIGN AND SETTING: A cross-sectional retrospective study conducted at a public university hospital in Campinas (Brazil) METHODS: All men aged 20–40 years with non-obstructive azoospermia were included in the analysis. RESULTS: The 107 cases included 14 with Klinefelter syndrome (KS) (13%), 1 with mosaic KS, 4 with sex development disorders (2 testicular XX, 1 NR5A1 gene mutation, and 1 mild androgen insensitivity syndrome) (4%), 9 with other non-obstructive azoospermia etiologies (8%), and 79 with undefined causes. The 22 chromosomal anomaly cases (14 KS, 1 mosaic KS, 2 testicular XX, 4 sex chromosome anomalies, and 1 autosomal anomaly) were compared with the 79 undefined cause cases. The KS group had lower average testicular volume, shorter penile length, and lower total testosterone levels but greater height, arm span, serum luteinizing hormone (LH) and follicle stimulating hormone (FSH) levels, and gynecomastia frequency (absent in the undefined group and affecting more than half of the KS group). Patients with testicular XX DSD had LH, FSH, and penile length data intermediate between the KS and undefined cause groups, testicular volume similar to the KS group, and other data similar to the undefined group. CONCLUSION: Clinical and laboratory data differentiate men with non-obstructive azoospermia and chromosomal anomalies, particularly KS and testicular XX, from those with undefined causes or other chromosomal anomalies.